Respuesta :
Answer:
[tex](x + 4)(x-4)=x^2-16\\(x + 2y)(x^2-2xy + 4y^2)=x^3+ 8y^3\\4x^2 + 12xy + 9y^2=\left (2x+3y \right )^2\\8x^3 + 12x^2 + 6x + 1=(2x+1)^3[/tex]
Step-by-step explanation:
Algebraic Operations
Performing some basic algebraic operations we can transform expressions into others which could be more convenient to handle. For example, a polynomial can be factored for future simplifications or conclusions about its roots.
We have the following expressions and its operations to make them look like their equivalents
1.
[tex](x + 4)(x-4)[/tex]
We use the notable or special product to simplify:
[tex](x + 4)(x-4)=x^2-16[/tex]
2.
[tex](x + 2y)(x^2-2xy + 4y^2)[/tex]
Performing the indicated products
[tex](x + 2y)(x^2-2xy + 4y^2)=x^3-2x^2y + 4xy^2+2yx^2-4xy^2 + 8y^3[/tex]
Simplifying
[tex]x^3+ 8y^3[/tex]
3.
[tex]4x^2 + 12xy + 9y^2[/tex]
This is the square of a binomial. We find the square root of the first and last terms, then we test the second to be double of their product
[tex]\sqrt{4x^2}=2x[/tex]
[tex]\sqrt{9y^2}=3y[/tex]
[tex]2(2x)(3y)=12xy[/tex]
Since all the terms are correct, we can express it like
[tex]\left (2x+3y \right )^2[/tex]
4.
[tex]8x^3 + 12x^2 + 6x + 1[/tex]
This is the cube of a binomial. Let's find the cubic root of the first and last term
[tex]\sqrt[3]{8x^3}=2x[/tex]
[tex]\sqrt[3]{1}=1[/tex]
The binomial is (2x+1). To prove it's correct, let's expand
[tex](2x+1)^3=8x^3 + 12x^2 + 6x + 1[/tex]
Thus, the expressions must be matched like this
[tex](x + 4)(x-4)=x^2-16\\(x + 2y)(x^2-2xy + 4y^2)=x^3+ 8y^3\\4x^2 + 12xy + 9y^2=\left (2x+3y \right )^2\\8x^3 + 12x^2 + 6x + 1=(2x+1)^3[/tex]